2020
DOI: 10.21164/pomjlifesci.588
|View full text |Cite
|
Sign up to set email alerts
|

The level of acceptance of the illness among patients with psoriasis

Abstract: Introduction: Psoriasis is a chronic inflammatory and non-infectious skin disease. It is one of the most common dermatoses. Increased reproduction of the epidermis and, as a consequence, visible skin lesions negatively affect the patient's psyche, disrupt self-esteem, reducing the chance of accepting the disease and a normal life.The aim of this study was the assessment of the level of acceptance of the illness and identification of factors affecting its acceptance among patients with psoriasis.Materials and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Similarly, a cross-sectional survey conducted among psoriasis patients from 12 Arabic countries including Egypt, found that 25.4% and 35.9 % of patients reporting a low and moderate acceptance of psoriasis (29) . Conversely, the studies of Kowalewska et al (34) and Budzińska et al (35) in Poland revealed that most psoriasis patients showed high and moderate levels of psoriasis acceptance. This variance could be due to the extent of psoriasis and how it affects the patients' daily life and relationships.…”
Section: Discussionmentioning
confidence: 89%
“…Similarly, a cross-sectional survey conducted among psoriasis patients from 12 Arabic countries including Egypt, found that 25.4% and 35.9 % of patients reporting a low and moderate acceptance of psoriasis (29) . Conversely, the studies of Kowalewska et al (34) and Budzińska et al (35) in Poland revealed that most psoriasis patients showed high and moderate levels of psoriasis acceptance. This variance could be due to the extent of psoriasis and how it affects the patients' daily life and relationships.…”
Section: Discussionmentioning
confidence: 89%